How Adelaide Hasse Got Fired: A Feminist History of Librarianship through the Story of One Difficult Woman, 1889-1953 - Beck, Clare (My University, 2008)
Adelaide Hasse was one of the most prominent and certainly the most controversial of the first generation of women librarians in the era of the New Woman. Best known for her work with government publications, she also was involved in most of the major issues of a developing profession, seldom missing an opportunity to make provocative comments. Her career swung dramatically between highs and lows, most notably in being summarily dismissed by New York Public Library after twenty-one years of distinguished service, but she always fought back and bounced back. Clare Beck, author of The New Woman as Librarian: the Career of Adelaide Hasse (Scarecrow Press, 2006), discusses her experience in researching and writing the life of a woman librarian and suggests how biography can both illuminate the construction of a gendered profession and provide fresh perspective on issues of continuing concern to librarians. Clare Beck is emeritus professor at Eastern Michigan University, Ypsilanti, where she served for many years as a government documents librarian.
Lecture delivered by Clare Beck on October 8, 2008, 1-3:00 p.m., Petersen Room, Suzzallo & Allen Libraries, University of Washington. Lecture begins at 5 minutes 38 seconds into audio file. Introduction by Cass Hartnett, U.S. Documents Librarian, University of Washington Libraries
Keywords: Adelaide Hasse, history of librarianship, feminism, government documents, women librarians, biography